PENGARUH HARGA DAN KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN DIMASA PANDEMI COVID-19 PADA BENGKEL HONDA NSS AHASS 1838 KARAWANG - Muhamad Jumhari (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This study aims to determine the effect of price and quality of service on customer satisfaction at the Honda NSS Ahass 1838 workshop Karawang. The research method used is descriptive verification with a quantitative approach. The research sample is 100 consumers, using incidental sampling. The analysis used is path analysis and hypothesis testing using t test and F test. The results of this study indicate that there is a correlation between price and service quality of 0.258, which means there is a weak relationship. The results of the partial hypothesis test that price has a positive and significant effect on customer satisfaction, service quality has a positive and significant effect on customer satisfaction. The results of the hypothesis that simultaneously price and service quality have a significant effect on customer satisfaction. The R2 test of price and service quality on consumer satisfaction obtained R Square of 0.779, meaning that 77.9% of consumer satisfaction was influenced by these two variables, while 22.1% of consumer satisfaction was influenced by other variables not examined in this study.